Bullying's Impact on Mental Health of Islamic Boarding School Students in Dormitories - Karmila, Lisa Puspa; Martha, Evi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Islamic boarding schools as religious-based educational institutions have an important role in shaping the character and personality of students. However, increasingly intensive interactions in the dormitory environment and social pressure between students often create conditions that are vulnerable to bullying behavior, both verbal and physical. This study highlights the impact of bullying on the mental health of students in the Islamic boarding school environment, where intimidation behavior can trigger anxiety disorders, depression, and decreased self-esteem. Methods The study used a systematic review method using PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis). database search by searching for articles from 3 databases, namely Google Scholar, Science Direct and Scopus. Obtained 162 articles with the keywords